A Mutation in IL4RA Is Associated with the Degree of Pathology in Human TB Patients - Christoph Hölscher; Lisa Heitmann; Ellis Owusu-Dabo; Rolf D. Horstmann; Christian G. Meyer; Stefan Ehlers; Thorsten Thye (Mediators of Inflammation)
The contribution of interleukin- (IL-) 4 receptor-alpha- (Rα-) dependent events in the pathogenesis of tuberculosis (TB) is controversial. We have recently shown IL-13 overexpression in mice to cause recrudescent Mtb replication and centrally necrotizing granulomas strongly resembling pathology of human TB. A deletion of IL-4Rα completely abrogates TB tissue pathology in these mice. To validate our results in human TB patients, we here determined the association of distinct variants of the IL4, IL13, IL4RA, IL13RA1, and IL13RA2 genes with cavity formation in a large Ghanaian cohort of HIV-negative individuals with newly diagnosed pulmonary TB. In fact, the structural variant of the IL4RA I50V, previously shown to result in enhanced signal transduction, was significantly associated with greater cavity size, and a variant of IL13RA2 was associated with disease in females. To evaluate whether the human-like TB pathology in IL-13-overexpressing mice is specifically mediated through the IL-4Rα subunit, we analyzed IL-13 transgenic mice with a genetic ablation of the IL-4Rα. In these mice, the IL-13-mediated increased susceptibility, human-like pathology of collagen deposition around centrally necrotizing granulomas, and alternative macrophage activation were abolished. Together, our genetic association study in human TB patients further supports the assumption that IL-13/IL-4Rα-dependent mechanisms are involved in mediating tissue pathology of human TB.